Pelaksanaan Sistem Simpada dan Sipakbumibana dalam Pembayaran Pajak Bumi dan Bangunan di BPKPD Kota Pariaman - Maulidya Alfi Utami; Syamsir Syamsir; Mutiara Astika; Muhammad Farhan Shafly; Alif Alif; Iis Mardiana Firjayanti; Vira Farisa Risman; Hudmi Hudmi; Adinda Qawlam Desfa Sahfitri (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The Pariaman City Government decided to apply technology in public services to improve efficiency and quality of service to the community. This is done to meet society's increasing demands for fast, effective and efficient services. This research uses a descriptive qualitative approach. The qualitative descriptive approach is a research approach where the data collected is in the form of words, images and not numbers. This data can be obtained from interviews, field notes, photos, video tapes, personal documentation, notes or memos, and other documents. The aim of public services is to provide fair, equitable, timely, effective, efficient and transparent services to the community. Regional financial management involves several stages, such as planning, budgeting, implementation, accountability and supervision of regional finances. In regional financial management, there are several applications and systems used. For example, SISMIOP and Sipakbumibana are used to manage Land and Building Tax (PBB), SIMBPHTB are used to manage Land and Building Rights Acquisition Fees (BPHTB), and SIMPADA is used to manage regional income. There are three important elements in regional financial management, namely BAPPEDA, BPKPD, and DISPECTORATE, each of which has its own responsibilities. several regulations governing regional financial management, such as PP 12 of 2019, Permendagri 70 of 2020, and Law 1 of 2022.